MEAT BONE MEAL (MBM) AND POLTRY BY-PRODUCT (PBM) TEST ON GRANULE TOWARDS THE GROWTH AND SURVIVAL RATE OF EEL (Anguilla Bicolor) Stadia ELVER - Triana Indri Astuti; Hany Handajani; Riza Rahman Hakim (Universitas Muhammadiyah Malang, 2018)
This research was conducted at Hatchery Fishery Laboratory in University of Muhammadiyah Malang on February 15 - March 17, 2018. The purpose of this research was to identify the meat bone meal (MBM) and poltry by-product (PBM) test on granule and the best treatment to the growth and survival rate of Eel (Anguilla bicolor) stadia elver. The method used was experiemental by Completely Randomized Design (RAL) with 3 different treatments on granule composition, P1 (Commercial Granule), P2 (70% Commercial Granule and 30% MBM), P3 (70% Commercial Granule and 30% PBM), and each treatment done repeatedly three times. Furthermore, the data were analyzed by ANAVA and continued with BNT test. The results of this study indicated that the meat bone meal (MBM) and poltry by-product (PBM) test on granule had a significant effect on the absolute growth rate, a very significant effect on DGR, and not significantly different on Eel. The absolute best growth rate was on P2 2.24 ± 0.71. The best DGR was on P1 (5.55 ± 0.33). Based on the research results, it was concluded that feeding the granule based on meat bone meal increased the growth and survival rate, and also could be the substitution granule for Eel ( Anguilla bicolor). Keywords: Anguilla bicolor, MBM, PBM, Growth